Comparative transcriptomic and molecular biology analyses to explore potential immune responses to Vibrio parahaemolyticus challenge in Eriocheir sinensis - Chen, Duanduan; Xin, Yunteng; Teng, Jian; Zhao, Xiaodong; Lu, Jianbiao; Li, Yubao; Wang, Hui (Frontiers in Cellular and Infection Microbiology, 2024)
Vibrio parahaemolyticus is a significant pathogen affecting shrimp and crab farming, particularly strains carrying genes associated with acute hepatopancreatic necrosis syndrome. However, the immune response of Eriocheir sinensis to V. parahaemolyticus infection remains unclear. To address this knowledge gap, an experiment was conducted to establish a V. parahaemolyticus infection model. This model aimed to compare pathological damage and enzyme activity changes in E. sinensis hepatopancreas tissue at various infection time points, and to examine transcriptome changes in individuals exhibiting different clinical symptoms of infection. The results showed that intramuscular injection of 1.78 × 106 CFU/mL of V. parahaemolyticus for 24 hours resulted in a 50% mortality rate among the experimental animals. Pathological findings revealed that the infection led to a change in color of the hepatopancreas tissue from bright yellow to white, diffuse tissue cell distribution, and hepatopancreatic necrosis. Additionally, there was a significant increase in the activities of alanine aminotransferase and aspartate aminotransferase in the hepatopancreas (P < 0.01). Furthermore, the activities of superoxide dismutase, total antioxidant capacity, phenoloxidase, alkaline phosphatase, and acid phosphatase initially increased and then decreased. RNA-seq analysis revealed 11,662 differentially expressed genes compared to the susceptible group and control group, with 6,266 genes up-regulated and 5,396 genes down-regulated. When comparing the susceptible group to the disease-resistant group, 13,515 differentially expressed genes were identified, with 7,694 genes up-regulated and 5,821 genes down-regulated. Finally, comparison between the disease-resistant group and control group yielded 13,515 differentially expressed genes, with 7,631 genes up-regulated and 3,111 genes down-regulated. Differential gene enrichment analysis revealed pathways such as phagosomes, cancer pathways, proteoglycans in cancer, ribosomes, protein processing in the endoplasmic reticulum, starch and sucrose metabolism, and lysosome signaling pathways. Furthermore, 342 immune-related genes with differential expression were identified, primarily enriched in 22 pathways linked to cell signaling. These genes play a crucial role in defense against bacterial invasion and immune response regulation through various signaling pathways. Overall, this study provides valuable insights into the defense mechanisms and understanding of Chinese mitten crab immunity against bacterial infection by examining changes in mRNA, enzyme activity, and hepatopancreatic damage during infection.